Learner− content interaction in distance learning models: students' experience while using learning management systems - Malinovski, Toni; Lazarova, Maja; Trajkovik, Vladimir (Inderscience Publishers Ltd, 2012)
Distance education or distance learning is a process that provides access to learning when the source of information and the learners are separated by time and distance. It is a field of education that focuses on the involvement of technology and the social aspect, while delivering knowledge and training to students over distance. This study focuses on the social aspect regarding learner–content interaction in distance learning models, evaluates several learning managements systems while investigating the relations among different variables which impact the degree of students’ learning experiences. A survey among students in different universities was conducted, Structural Equation Model (SEM) was created and analysed with Confirmatory Factor Analysis (CFA), for better understanding of the factors which predicts student satisfaction from such learning environments. Research findings illustrate the relationship among usability, adaptability of the system and students’ experience. Limitations to the research and recommendations for future research are also being discussed.
Keywords: distance education; learner–content interaction; students’ experience; survey; SEM; structural equation model; learning management systems